1998
DOI: 10.1093/ije/27.2.231
|View full text |Cite
|
Sign up to set email alerts
|

Night blindness of pregnancy in rural Nepal--nutritional and health risks

Abstract: Women who experience XN during pregnancy have a low vitamin A status, although several other risk factors appear to cluster among these women as well. Night blind women are also more likely to be anaemic, ill, and acutely under-nourished, and to be consuming a nutritionally poorer diet in pregnancy than non-night blind pregnant women. A simple history of XN can identify women at high risk during pregnancy who may require special nutritional support, antenatal care and counselling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
111
0
23

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(140 citation statements)
references
References 25 publications
6
111
0
23
Order By: Relevance
“…Women were asked to recall the number of times they had consumed 38 different types of vitamin A-and carotenoid-rich foods from a list that was developed using formative research on commonly consumed sources of vitamin A and b-carotene in this area of Nepal. Previously, we have shown that vitamin A and b-carotene food intakes, using the 7-day food frequency recall, were significantly associated with functional and biochemical indicators of vitamin A status such as maternal night blindness (Christian et al, 1998b) and low serum retinol (West et al, 1999) and carotenoid concentrations (Yamini et al, 2001). Mid-upper-arm circumference (MUAC), as a measure of nutritional status, was measured at both times.…”
Section: Methodsmentioning
confidence: 99%
“…Women were asked to recall the number of times they had consumed 38 different types of vitamin A-and carotenoid-rich foods from a list that was developed using formative research on commonly consumed sources of vitamin A and b-carotene in this area of Nepal. Previously, we have shown that vitamin A and b-carotene food intakes, using the 7-day food frequency recall, were significantly associated with functional and biochemical indicators of vitamin A status such as maternal night blindness (Christian et al, 1998b) and low serum retinol (West et al, 1999) and carotenoid concentrations (Yamini et al, 2001). Mid-upper-arm circumference (MUAC), as a measure of nutritional status, was measured at both times.…”
Section: Methodsmentioning
confidence: 99%
“…VAD has adverse effects on health, particularly during infancy, childhood and pregnancy because of the rapid growth, proliferation and tissue development that happen in these phases of life. Vitamin A deficient women were found to be more susceptible to illnesses of both infectious such as frequent infection of mucous surface of hallow viscera (Christian et al, 1998) and non-infectious (eclampsia, pre-eclampsia, premature rupture of membrane) nature (Mikhail et al, 1994;Barrett et al, 1994;Ziari et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Tal valor está sendo aplicado com freqüência crescente para definir a deficiência da vitamina A em gestantes, puérperas, recém-nascidos, pré-escolares e escolares (3,10,13,14) . Ressalta-se que esse ponto de corte já foi inter-validado com o teste terapêutico (+S30DR) e com o RDR (28) , além de apresentar associação com alterações funcionais da visão (11,12,27,30,31) . O International Vitamin A Consultive Group também registrou diversos estudos que reforçam a utilização do referido ponto de corte para diagnosticar a deficiência da vitamina A em variados grupos populacionais (32) .…”
Section: Discussionunclassified